The tiger salamander as a promising alternative model organism to the axolotl for fracture healing and regenerative biology research - Bothe, Vivien; Fröbisch, Nadia (Anatomical record (Hoboken, N.J. : 2007), 2025)
Scientists have been captivated by the ability to regenerate, focusing on uncovering the mechanisms of epimorphic regeneration and applying them to human medicine. The axolotl ( Ambystoma mexicanum ) has become the most intensively studied model in tetrapod regeneration research, particularly concerning limb regeneration. This research has provided significant insights into signaling pathways and factors regulating limb regeneration. However, most regeneration studies focus on controlled, surgical amputation experiments under strict laboratory conditions. This practice has limited the available data on natural bite‐induced regeneration, which, however, is crucial for understanding the natural condition in wild populations and provides insights into the biology and evolution of regenerative capacities. Moreover, the axolotl's paedomorphic life history limits the generalization of findings to other salamander taxa. This study compares limb regeneration in axolotls and their metamorphosing sister taxon, the tiger salamander ( Ambystoma tigrinum ), across various ontogenetic stages to identify common and variable aspects of the regeneration process, providing a basis for future comparative studies in different salamander taxa. The results demonstrate that tiger salamanders have excellent regenerative capacity during the larval stage, which is in no way inferior to that of axolotls. Post‐metamorphic tiger salamanders are still able to regenerate limbs. However, there is a clear slowdown in the speed of regeneration and an increase in skeletal anomalies. Axolotls are often subject to bite attacks even in the adult stage. This leads to severe pathologies in the limb anatomy after regeneration, up to severely restricted movement or non‐functional limbs.